KEPENTINGAN CINA MENOLAK IMPOR MANGGIS INDONESIA TAHUN 2013 - Siboro, Irvandus; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The objective of this research is to discuss the interest of China in refusing imports of mangosteen fruits from Indonesia in 2013. China is the largest market for mangosteen, ass well as the largest horticulture exporter for Indonesia. However, after the enactment of ASEAN-China Free Trade Area (ACFTA), Indonesia is flooded by imports horticulture products. Hence, in 2012 Indonesian government issued 4 cross- sector regulations for domestic product protection.The theoretical framework used in this research is neo-mercantilism, which discusses the theory of protection in forms of tariff barrier and nontariff barrier. This research uses qualitative approach with literature study data collection method. This research uses primary and secondary data. Primary data were obtained from the Ministry of Agriculture, Ministry of Commerce, the Central Bureau of Statistics and other primary documents. While secondary data were obtained from books, articles, journals and printed and online mass media. Level of analysis used in this research is nation state concept. Based on results the analysis of the theoretical framework, it can be concluded that there are correlations between Indonesian horticulture protection against the ban on China’s mangosteen import from Indonesia. Moreover, it can also be seen that China wants a Mutual Recognition Agreement (MRA) with Indonesia.Keywords: ACFTA, Horticulture, Interest, Mangosteen, MRA, Protection